2010
DOI: 10.1002/hyp.7571
|View full text |Cite
|
Sign up to set email alerts
|

Modelling investigation of water partitioning at a semiarid ponderosa pine hillslope

Abstract: Abstract:The effects of vegetation root distribution on near-surface water partitioning can be two-fold. On the one hand, the roots facilitate deep percolation by root-induced macropore flow; on the other hand, they reduce the potential for deep percolation by root-water-uptake processes. Whether the roots impede or facilitate deep percolation depends on various conditions, including climate, soil, and vegetation characteristics. This paper examines the effects of root distribution on deep percolation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(50 reference statements)
2
10
0
2
Order By: Relevance
“…Sansoulet et al (2008) similarly found that stemflow caused the infiltration rates around a banana stem to be up to six times higher than in the throughfall areas. Several other studies observed differences between stemflow and throughfall rates, including for olive trees (Gomez et al, 2002), banana plants (Cattan et al, 2009), tall stewartia (Liang et al, 2009), and ponderosa pine (Guan et al, 2010). While all of the above studies point to significant differences between the stemflow and throughfall rainfall rates, noticeably lacking are studies about possible differences in the soil hydraulic properties of the stemflow and throughfall areas, which should further exacerbate differences in the local infiltration rates.…”
Section: Introductionmentioning
confidence: 97%
“…Sansoulet et al (2008) similarly found that stemflow caused the infiltration rates around a banana stem to be up to six times higher than in the throughfall areas. Several other studies observed differences between stemflow and throughfall rates, including for olive trees (Gomez et al, 2002), banana plants (Cattan et al, 2009), tall stewartia (Liang et al, 2009), and ponderosa pine (Guan et al, 2010). While all of the above studies point to significant differences between the stemflow and throughfall rainfall rates, noticeably lacking are studies about possible differences in the soil hydraulic properties of the stemflow and throughfall areas, which should further exacerbate differences in the local infiltration rates.…”
Section: Introductionmentioning
confidence: 97%
“…Figure compares trench runoff observations with simulated values at the hillslope outlet with no additional calibration. The model is able to capture the major events during the 1993–1994 summer season (see Guan et al ., , for a similar comparison). However, the model overestimates runoff during the 1992–1993 water year (with the potential reason being inaccurate runoff data transcription).…”
Section: Resultsmentioning
confidence: 99%
“…Guan et al (2010) demostraron que en suelos arcillosos y bajo ciertas condiciones, la presencia de raíces de árboles favorece la recarga del suelo y los mantos freáticos, posibilitando una percolación hasta del 20 % de la precipitación anual, mientras que sin presencia de este tipo de vías preferenciales de infiltración la percolación es < 1 %. Si bien la determinación de los procesos de infiltración, recarga edáfica y de acuíferos se encuentra fuera del alcance de este trabajo, de acuerdo con las condiciones del suelo en el área de estudio, es posible que mecanismos similares a los descritos por Guan et al (2010) estén ocurriendo.…”
Section: Discussionunclassified
“…Guan et al (2010) demostraron que en suelos arcillosos y bajo ciertas condiciones, la presencia de raíces de árboles favorece la recarga del suelo y los mantos freáticos, posibilitando una percolación hasta del 20 % de la precipitación anual, mientras que sin presencia de este tipo de vías preferenciales de infiltración la percolación es < 1 %. Si bien la determinación de los procesos de infiltración, recarga edáfica y de acuíferos se encuentra fuera del alcance de este trabajo, de acuerdo con las condiciones del suelo en el área de estudio, es posible que mecanismos similares a los descritos por Guan et al (2010) estén ocurriendo. Los resultados ponen de manifiesto la necesidad de evaluar el aporte del índice de escorrentía cortical y escorrentía cortical en el balance hídrico a escala local, de cuenca y su posible influencia en la recarga edáfica y de acuíferos, como ha sido descrito previamente por varios investigadores (Návar 2011).…”
Section: Discussionunclassified